Sensitivity and specificity of a rapid influenza diagnostic test in children and clinical utility during influenza A (H1N1) 2009 outbreak. Issue 11 (13th October 2010) - Angoulvant, F; Bellettre, X; Houhou, N; Dexpert, J B; Morin, L; Siriez, J Y; Soole, F; de Lauzanne, A; Cohen, R; Brun-Vezinet, F; Alberti, C; Mercier, J C
Abstract : Introduction: The influenza A (H1N1) 2009 outbreak caused death and a disruption of public health services. Rapid influenza diagnostic tests (RIDT) could be helpful to ease the triage of patients and prevent an overload of emergency and laboratory facilities. Objectives: To compare the sensitivity and specificity of the Clearview Exact Influenza A&B test and real-time reverse transcription(RT)–PCR to detect influenza A (H1N1) 2009 in a paediatric emergency department of a paediatric teaching hospital in Paris, France. Methods: 76 children with an influenza-like illness and either severe symptoms or an underlying medical condition were prospectively recruited between July 2009 and October 2009. RIDT and RT–PCR were simultaneously performed and compared. Results: Among 39 influenza A (H1N1) 2009 RT–PCR-positive children (median age 5 years), 23 Clearview Exact Influenza A&B tests were positive. Sensitivity was 59% (95% CI 42.2 to 74) and specificity was 94.6% (95% CI 80.5 to 99.1). Conclusions: This study shows a sensitivity of RIDT of 59%, in agreement with other prospective studies, which could be useful in clinical practice for diagnosis influenza A (H1N1) 2009 in children. In outbreaks of a high prevalence, such as the 2009 outbreak, this test can help to prevent an overload of public health services.